PENGARUH KREATIVITAS GURU TERHADAP PEMANFAATAN MEDIA PEMBELAJARAN TEMATIK - Faridah Karyati (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2016)
A critical factor in enhancing creativity in school is the teacher's role. There are so many things that teachers can do in schools to stimulate and improve the thinking of students, attitudes and behaviors of creative students, through activities within or outside the classroom Learning thematic require creative teacher both in preparing activities or learning experiences for students, also in choosing the competence of various subjects and set it so that learning becomes more meaningful, interesting, fun and intact. The subjects in this study are teachers at SDN 5 Banjarbaru City. digger tool data used questionnaires with data analysis techniques using simple linear regression. There are significant research results indicating the creativity of teachers on the utilization of instructional media in thematic learning in SDN Banjarbaru City 5 with the degree of influence by 9.2% and the rest influenced by other factors.It is recommended for teachers who do not take advantage of learning media can optimally utilize the media planning for learning and for the principal to be planning a program to learn to prioritize the procurement of instructional media in any learning activities in an effort to boost the creativity of teachers